PENGARUH FREE CASH FLOW, STRUKTUR ASET, LIKUIDITAS, PROFITABILITAS, PERTUMBUHAN PENJUALAN, DAN RISIKO BISNIS TERHADAP KEBIJAKAN HUTANG (Studi Empiris Perusahaan Sektor Industri Barang Konsumsi yang Terdaftar di BEI 2016-2020) - Nurkholik, Nurkholik; Khasanah, Kharirotul (Faculty of Economic and Business Universitas STIKUBANK, 2022)
This study aims to determine the effect of Free Cash Flow, Asset Structure, Liquidity, Profitability, Sales Growth, and Business Risk on Debt Policy in Manufacturing Companies in the Consumer Goods Industry Sector Listed on the IDX in 2016-2020. The population in this study are manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2016-2020 period, namely 53 companies. The samples taken were 24 manufacturing companies. Sampling was done by purposive sampling technique. The variables in this study are Free Cash Flow, Asset Structure, Liquidity, Profitability, Sales Growth, and Business Risk as independent variables and Debt Policy as the dependent variable. The data analysis technique used in this research is multiple linear regression analysis with classical assumption test. Partial test results show that Free Cash Flow has no effect on debt policy, Asset Structure has no effect on debt policy, Liquidity affects debt policy, Profitability affects debt policy, Sales Growth does not affect debt policy, and Business Risk affects debt policy . Meanwhile, simultaneous testing shows that Free Cash Flow, Asset Structure, Liquidity, Profitability, Sales Growth, and Business Risk have an effect on Debt Policy.